Global Trends and Research Frontiers in Project-Based Learning: A Scopus-Based Bibliometric Review - Hambali, Hilmi; Bancong, Hartono; Sukmawati, Sukmawati (PPSDP International Journal of Education, 2025)
The aim of this study is to analyse the development of publications of scientific articles focusing on the project-based learning model. The method used is a literature review with a bibliometric analysis approach. A keyword search in the Scopus journal database for “Project-Based Learning; Science Education” was used to start the research. An analysis was carried out using the Vosviewer application, which allows in-depth exploration of trends and key contributions in the field. The results showed that a total of 702 publications were recorded in Scopus-indexed journals over a fifteen-year period, from 2010 to 2024. The United States emerged as the country that contributed the most publications, followed by Indonesia in second place, reflecting its active role in promoting research related to the Project based learning model. Among researchers, Capraro, Robert M. was identified as the most prolific contributor during the period 2010-2024. In addition, the keyword ‘project-based learning’ appeared most frequently in the articles, confirming its centrality in discussions of innovative educational practices. These findings suggest a significant and growing interest in Project Based Learning in science education. However, this study highlights the need for a broader scope of research. Future research should not be limited to Scopus-indexed journals, but should also include various databases and resources.